16O/18O Exchange of Aldehydes and Ketones caused by H218O in the Mechanistic Investigation of Organocatalyzed Michael, Mannich, and Aldol Reactions. Issue 17 (10th March 2016) - Hayashi, Yujiro; Mukaiyama, Takasuke; Benohoud, Meryem; Gupta, Nishant R.; Ono, Tsuyoshi; Toda, Shunsuke
Abstract: Organocatalyzed Michael, Mannich, and aldol reactions of aldehydes or ketones, as nucleophiles, have triggered several discussions regarding their reaction mechanism. H2 18 O has been utilized to determine if the reaction proceeds through an enamine or enol mechanism by monitoring the ratio of 18 O incorporated into the final product. In this communication, we describe the risk of H2 18 O as an evaluation tool for this mechanistic investigation. We have demonstrated that exchange of 16 O/ 18 O occurs in the aldehyde or ketone starting material, caused by the presence of H2 18 O and amine catalysts, before the Michael, Mannich, and aldol reactions proceed. Because the newly generated 18 O starting aldehydes or ketones and 16 O water affect the incorporation ratio of 18 O in the final product, the use of H2 18 O would not be appropriate to distinguish the mechanism of these organocatalyzed reactions. Abstract : Exchange of 16 O/ 18 O occurs in the aldehyde or ketone starting material in the presence of H2 18 O and amine catalysts before the organocatalyzed Michael, Mannich, and aldol reactions proceed. Because the newly generated 18 O starting aldehyde or ketone and 16 O water affect the incorporation ratio of 18 O in the final product, the use of H2 18 O would not be appropriate for distinguishing between the enamine and enol pathway for these types of transformation (see scheme).